2001
DOI: 10.1083/jcb.153.2.243
|View full text |Cite
|
Sign up to set email alerts
|

Desmoglein Isoform Distribution Affects Stratum Corneum Structure and Function

Abstract: Desmogleins are desmosomal cadherins that mediate cell–cell adhesion. In stratified squamous epithelia there are two major isoforms of desmoglein, 1 and 3, with different distributions in epidermis and mucous membrane. Since either desmoglein isoform alone can mediate adhesion, the reason for their differential distribution is not known. To address this issue, we engineered transgenic mice with desmoglein 3 under the control of the involucrin promoter. These mice expressed desmoglein 3 with the same distributi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
103
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(109 citation statements)
references
References 28 publications
6
103
0
Order By: Relevance
“…Transgenic mice also contained a compacted stratum corneum (Fig. 2B,D, *) similar to that of the Inv-mDsg3 transgenic mice previously described (Elias et al, 2001). The irregular and fragmented stratum corneum of Inv-Dsg2 transgenic epidermis was similar in appearance to that observed in dry scaly skin where stratum corneum production occurs at a faster rate than normal (Harding, 2004).…”
Section: Characterization Of Transgene Expression In Inv-dsg2 Transgementioning
confidence: 54%
See 1 more Smart Citation
“…Transgenic mice also contained a compacted stratum corneum (Fig. 2B,D, *) similar to that of the Inv-mDsg3 transgenic mice previously described (Elias et al, 2001). The irregular and fragmented stratum corneum of Inv-Dsg2 transgenic epidermis was similar in appearance to that observed in dry scaly skin where stratum corneum production occurs at a faster rate than normal (Harding, 2004).…”
Section: Characterization Of Transgene Expression In Inv-dsg2 Transgementioning
confidence: 54%
“…This was less prominent in the Inv-Dsg2 transgenic skin. Similar to the InvmDsg3 transgenic mice (Elias et al, 2001), we observed a high number of electron dense intercellular structures (Fig. 3B, arrowheads) that became detached (Fig.…”
Section: Characterization Of Transgene Expression In Inv-dsg2 Transgementioning
confidence: 67%
“…Misexpression of Dsg3 using the keratin 1 promoter to drive expression in the suprabasal epidermal layers in transgenic mice resulted in epidermal hyperproliferation and abnormal differentiation (Merritt et al 2002). Furthermore, expressing Dsg3 in the upper layers of the epidermis using the involucrin promoter resulted in an even more severe phenotype, including a resemblance to oral mucosa, a reduction in epidermal barrier function, and early postnatal lethality because of extensive water loss (Elias et al 2001). More recently, Dsg2 misexpression in the differentiated layers of the epidermis was found to cause hyperproliferation and susceptibility to chemically induced carcinogenesis (Brennan et al 2007).…”
Section: Role Of Desmosomal Cadherins In Epithelial Differentiationmentioning
confidence: 99%
“…At the genetic level, the loss of barrier function can be caused by an array of defects in the complex machinery required for the proper assembly of keratin ®laments in the corneocyte, the assembly of corni®ed envelope components, the formation of corneocyte adherens junctions, or the assembly of intercorneocyte lipids, as observed in numerous inherited skin diseases or in transgenic mice with dominant or recessive mutations in epidermal components (Nemes and Steinert, 1999;Presland and Dale, 2000;Roop, 1995). Null, frameshift, or point mutations in genes encoding structural proteins of the corneocyte (e.g., keratins, loricrin), in components of the enzymatic machinery that process and cross-link these structural proteins (e.g., transglutaminase 1), in desmosomal cadherins linking corneocytes together (e.g., desmoglein), or in the enzymes that manufacture and process corni®ed envelope and intercorneocyte lipids (e.g., fatty aldehyde dehydrogenase, arylsulfatase C/cholesterol sulfatase) have all been reported to disrupt epidermal barrier function (De Laurenzi et al, 1996;Elias et al, 2001;Huber et al, 1995;Koch et al, 2000;Kubilus et al, 1979;Matsuki et al, 1998;Russell et al, 1995;Shapiro et al, 1978). The data presented in this paper strongly suggest that the abrogation of barrier function is related to abnormal extrusion of vesicular bodies in the transitional layer of the cornifying epidermis, which likely aects the formation of the specialized set of crosslinked intercorneocyte lipids that confer epidermal barrier function in conjunction with the corni®ed envelope.…”
Section: /7mentioning
confidence: 99%